2011
DOI: 10.2166/wh.2011.134
|View full text |Cite
|
Sign up to set email alerts
|

Microbial safety of air-dried and rewetted biosolids

Abstract: To assess microbial safety of treated sewage sludge (biosolids), we examined the inactivation of microbial indicators for potential bacterial, viral and protozoan pathogens. The levels of indicators were determined throughout the air-drying and storage phases of anaerobically digested sewage sludge. Samples were collected from two wastewater treatment plants (WWTPs) in Victoria, Australia. Established methods were applied for analysis of bacteria and coliphages, based on membrane filtration and layered plates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This is achieved by the treatment of sludge using effective processes to reduce or eliminate the pathogen content, supplemented by cropping and harvesting restrictions preventing use on crops that are in contact with the soil and may be consumed without cooking, and to permit the natural attenuation of pathogens in the soil (USEPA, 1994;DoE UK, 1996;ADAS, 2001;NRMMC, 2004;EPA Victoria, 2004;WHO, 2006). We have observed substantial decay of pathogen indicators during solar drying treatment of sludge, in line with regulation limits for applying sludge in Australia (Rouch et al, 2011b). Ascaris lumbricoides is an important human pathogen, which infects over a billion people worldwide, with most infections occurring in developing countries (Crompton, 2001;Bethony et al, 2006).…”
Section: Introductionsupporting
confidence: 75%
“…This is achieved by the treatment of sludge using effective processes to reduce or eliminate the pathogen content, supplemented by cropping and harvesting restrictions preventing use on crops that are in contact with the soil and may be consumed without cooking, and to permit the natural attenuation of pathogens in the soil (USEPA, 1994;DoE UK, 1996;ADAS, 2001;NRMMC, 2004;EPA Victoria, 2004;WHO, 2006). We have observed substantial decay of pathogen indicators during solar drying treatment of sludge, in line with regulation limits for applying sludge in Australia (Rouch et al, 2011b). Ascaris lumbricoides is an important human pathogen, which infects over a billion people worldwide, with most infections occurring in developing countries (Crompton, 2001;Bethony et al, 2006).…”
Section: Introductionsupporting
confidence: 75%
“…Although biosolids can harbour human pathogens, such as shiga toxin Escherichia coli and enteric viruses, these typically die-off within a 3-month period (Lang et al 2003;Pourcher et al 2007). Yet, clostridia, such as Clostridium perfringens, can persist over years by virtue of being in the dormant, resistant, endospore form (Apedaile 2001; Desmarais et al 2002;Rouch et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently this higher concentration decreased as the biosolids dried to 80% DS in the final study weeks [27]. Re-wetting of biosolids by rainfall events was examined by Rouch et al [28] in air-dry storage of anaerobically digested biosolids. Rouch et al [28] found an inverse relationship to the DS contents of the biosolids with regards to the survival of E. coli, enterococci and coliphages.…”
Section: Moisture Content Of Dewatered Biosolidsmentioning
confidence: 99%
“…Re-wetting of biosolids by rainfall events was examined by Rouch et al [28] in air-dry storage of anaerobically digested biosolids. Rouch et al [28] found an inverse relationship to the DS contents of the biosolids with regards to the survival of E. coli, enterococci and coliphages. Due to the growth of dormant or small residual populations of bacterial in the biosolids, bacterial regrowth could occur as cells become active upon rewetting [28].…”
Section: Moisture Content Of Dewatered Biosolidsmentioning
confidence: 99%